2018
DOI: 10.1002/ijch.201800051
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Based Nanoparticles

Abstract: Nanoparticles made of biodegradable polymers have outstanding merits as a drug delivery system. Polysaccharide-based nanoparticles have been well explored because of their safety, stability, biocompatibility, biodegradability and hydrophilicity. The present review emphasizes the efforts articulated to improve polysaccharide-based nano-particles as drug delivery tool for effective therapy and sitespecific targeting of mainly anticancer agents. This review updates reports of recent research on polysaccharides-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 122 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…It had been reported that chitosan and their oligomers could interact with negatively-charged agents such as tripolyphosphate (TPP) to form a series of nanosystems with various particle sizes and zeta potentials [ 145 ]. Due to its versatility to form nanosystems with different functions, along with its excellent biocompatibility, non-toxicity and mucoadhesiveness for enhancing drug absorption and bioavailability, chitosan is usually considered to be one of the most widely used polysaccharides in the nanomedicine field [ [146] , [147] , [148] ]. The generated chitosan-based nanomedicines usually have high biodegradability, excellent biocompatibility, bioactivity and polycationicity [ [149] , [150] , [151] ], thus they are effective nanocarriers for drug delivery applications [ [152] , [153] , [154] ].…”
Section: Chitosan-based Nanomedicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…It had been reported that chitosan and their oligomers could interact with negatively-charged agents such as tripolyphosphate (TPP) to form a series of nanosystems with various particle sizes and zeta potentials [ 145 ]. Due to its versatility to form nanosystems with different functions, along with its excellent biocompatibility, non-toxicity and mucoadhesiveness for enhancing drug absorption and bioavailability, chitosan is usually considered to be one of the most widely used polysaccharides in the nanomedicine field [ [146] , [147] , [148] ]. The generated chitosan-based nanomedicines usually have high biodegradability, excellent biocompatibility, bioactivity and polycationicity [ [149] , [150] , [151] ], thus they are effective nanocarriers for drug delivery applications [ [152] , [153] , [154] ].…”
Section: Chitosan-based Nanomedicinesmentioning
confidence: 99%
“…Modifications of dextran through the hydroxyl groups in the backbone chain would allow interactions with selective receptors and other therapeutic ligands or agents, and remain their biocompatibility, which makes it another excellent candidate for nano-delivery of therapeutic drugs to achieve efficient treatment of diseases [ [282] , [283] , [284] , [285] ]. Furthermore, it has been indicated that dextran could be utilized as an alternative for PEGylation to prevent interactions of nanomedicines with opsonin [ 147 , 286 ]. Due to these advantages of dextran, it is widely used for the formation of nanomedicines.…”
Section: Dextran-based Nanomedicinesmentioning
confidence: 99%
“…Biopolymers with dimensions ranging between 10 and 1000 nm can be used as nanoparticles (NPs). Recently, many researchers have sought the attention of biopolymers due to their biocompatibility, easy design and preparation, surface variations, and interesting biomimetic characteristics . A few recent studies through the application of nanomedicines from natural sources encompassing lipid nanocarriers for phenolic drug delivery, , polysaccharide nanocarriers and composite nanocarriers for better specificity, prolonged circulation, better bioavailability, and enhanced permeation rate (EPR) have been discussed. These polymers have created a unique niche and inefficient ability in drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…This property is at the origin of the viscoelastic character and the control of tissue hydration [ 3 , 4 ] and, as a primary component of extracellular matrix (ECM) vitreous humor and synovial fluid of vertebrates, functions as a scaffold for the organization of these biofluids. HA has become a carrier of great interest not only owing to its advantages such as biodegradability, biocompatibility, but also to its intrinsic targeting properties, based on the selective interactions with receptors, such as CD44 or hyaluronan receptors for endocytosis (HARE) [ 5 ]. For these reasons, exogenous HA has been investigated as a drug delivery system for therapeutics and diagnostics [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…HA has become a carrier of great interest not only owing to its advantages such as biodegradability, biocompatibility, but also to its intrinsic targeting properties, based on the selective interactions with receptors, such as CD44 or hyaluronan receptors for endocytosis (HARE) [ 5 ]. For these reasons, exogenous HA has been investigated as a drug delivery system for therapeutics and diagnostics [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%